Ethics‐in‐practice in fragile contexts: Research in education for displaced persons, refugees and asylum seekers. (28th March 2020) - Fox, Alison; Baker, Sally; Charitonos, Koula; Jack, Victoria; Moser‐Mercer, Barbara
Abstract : The rising numbers of forcibly displaced peoples on the move globally, and the challenges with providing access to education, reflect the shifting and complex times that we live in. Even though there has been a proliferation in educational research in the context of forced migration, in line with the increasing number of forced migrants, there has not been a commensurate focus on unpicking the increasingly complex ethical conditions within which researchers and participants operate. To examine this issue, the article provides three narrated accounts by researchers in this field and explores the interaction of researcher and author‐researcher voice to critically appraise their research experience and identify critical reflections of understanding of ethics‐in‐practice in fragile contexts. These narratives are framed by the CERD (consequential, ecological, relational and deontological) ethical appraisal framework, which explores ethical thinking through four ethical lenses. The article contributes to a deeper understanding of ethics‐in‐practice as a central dimension in educational research. The implications of this work show how a one‐size‐fits‐all approach to ethical appraisal is inappropriate for socially just educational research. This work also illustrates the importance of attending to relationships and voice of the forcibly displaced, both of which are often lacking in educational research in fragile contexts.